2020
DOI: 10.3389/fpls.2020.574674
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies Detect Multiple QTLs for Productivity in Mesoamerican Diversity Panel of Common Bean Under Drought Stress

Abstract: Drought stress is an important abiotic factor limiting common bean yield, with great impact on the production worldwide. Understanding the genetic basis regulating beans’ yield and seed weight (SW) is a fundamental prerequisite for the development of superior cultivars. The main objectives of this work were to conduct genome-wide marker discovery by genotyping a Mesoamerican panel of common bean germplasm, containing cultivated and landrace accessions of broad origin, followed by the identification of genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 148 publications
19
49
0
Order By: Relevance
“…Based on these initial studies, several GWAS have further been conducted for different traits of interest, such as yield, plant architecture, nutritional content of grains, cooking time, resistance to diseases, and tolerance to abiotic factors 7 , 32 , 37 47 . Some GWAS have been conducted in Brazil 37 , 40 , 48 , however, panels consisting of different genotypes, can contribute to a better understanding about the genetic diversity and relationships of the germplasm available for genetic breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these initial studies, several GWAS have further been conducted for different traits of interest, such as yield, plant architecture, nutritional content of grains, cooking time, resistance to diseases, and tolerance to abiotic factors 7 , 32 , 37 47 . Some GWAS have been conducted in Brazil 37 , 40 , 48 , however, panels consisting of different genotypes, can contribute to a better understanding about the genetic diversity and relationships of the germplasm available for genetic breeding.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic correlation coefficients for GY and other variables were higher in the NS experiment than in the DS experiment ( Table 3 ). Positive correlations between SYD and the yield components have previously been reported under drought conditions [ 8 , 33 , 34 , 35 ]. The GY was positively correlated with SYD (r = 0.73), NP (r = 0.65), and SW (r = 0.42).…”
Section: Resultsmentioning
confidence: 80%
“…Although several studies already identified QTNs associated with morpho-agronomic traits in common beans using GWAS (Nemli et al, 2014;Kamfwa et al, 2015;Moghaddam et al, 2016;Soltani et al, 2016;Nascimento et al, 2018;Resende et al, 2018;Lei et al, 2020;Wu et al, 2020), panels composed exclusively of common beans of Mesoamerican origin and adapted to environmental conditions in Brazil had not been sufficiently explored (Valdisser et al, 2020). Moreover, few studies using the GWAS multilocus approach have been conducted in common bean.…”
Section: Discussionmentioning
confidence: 99%